A Web-based Homework Monitoring System for Sekolah Rendah Bangsar - Amirul Fahmi, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2019)
This project aims to describe the proposed system of A Web-based Homework Monitoring System. Development of the proposed system is to solve the problem that occurs at home by parents who have kids at school. Some parents did not aware that their children have homework that needs to finish by a certain time given by the teachers. Moreover, some teacher did not have any platform to use to communicate formally to their student’s parents. In addition, the use of paper to spreading the news is one of the big challenges and issues faces by the school. This is because sometimes school might be running out of budget to buy the paper to use. As a result, some important news might be miss. With the new proposed system, the problem can be solved and a perfect way for the teacher and parents to manage their student’s homework.